#banggabuatanindonesia Social Marketing of #banggabuatanindonesia as Indonesian National Identity Campaign in Social Media - Pasaribu, Rotumiar (Ultimacomm: Jurnal Ilmu Komunikasi, 2023)
#banggabuatanindonesia is one of social marketing campaign activity which focus on building selling and buying habit for the Indonesian people. This activity is created to raise the Indonesian economic sector by campaigning the domestic product. The worries also came while the Indonesian people are prouder to use the product from foreign country. This problem brings the bad effect weather for the economic cycle of domestic product selling. Furthermore, this case also wants to solve the nation identity crisis from economic sector by campaigning #banggabuatanindonesia. The purpose of this campaign is to educate the seller who sell the product and the customer to be proud of domestic product. Beside make the cycle of nation economic more stable, this activity also aims to create Indonesia Nation Identity campaign by domestic product. This campaign uses social media to spread the information. From that information, this research wants to focus on the measurement of the campaign which use social marketing tool in social media with hashtag #banggabuatanindonesia. The measurement of the campaign uses input, output, outtake and outcome tools. The social marketing activities focus on marketing mix which consist of product, price, place and promotion. This research uses qualitative approach which focus on content analysis method. The result show that there are so many new account members which use #banggabuatanindonesia social marketing as promotion strategy and help campaigning Indonesia identity. That activity gives the lesson for the seller to create good domestic product and marketing activity. in other side, the consumer gets the lesson and can buy domestic product. As a result of understanding Indonesia nation identity, between the seller and consumer create #banggabuatanindonesia campaigning activity from transactional activity in social media. Finally, this activity gives good impact such as the development of selling domestic product, having Indonesia economic positive circulation and also establishing Indonesian nation identity campaign.